2017
DOI: 10.1097/ceh.0000000000000162
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Reflection and Behavior Change in CME

Abstract: To our knowledge, this is the first study to show a relationship between participant reflection and CTC in conference-based CME. Presentations that incorporate clinical cases and audience response systems seem to stimulate participant reflection and behavior change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 28 publications
2
20
0
Order By: Relevance
“…As one example, Commitment to Change (CTC) exercises encourage learners to formulate specific changes that they might like to implement into their practices after the completion of a course, given what they learned during the training. These CTC exercises have proven effective in many settings and have gained significant traction within the field of medicine (Domino, Chopra, Seligman, Sullivan, & Quirk, 2011; Ratelle et al, 2017). Step-by-step procedures for using the CTC measures can be found in Neimeyer et al (in press)…”
Section: Resultsmentioning
confidence: 99%
“…As one example, Commitment to Change (CTC) exercises encourage learners to formulate specific changes that they might like to implement into their practices after the completion of a course, given what they learned during the training. These CTC exercises have proven effective in many settings and have gained significant traction within the field of medicine (Domino, Chopra, Seligman, Sullivan, & Quirk, 2011; Ratelle et al, 2017). Step-by-step procedures for using the CTC measures can be found in Neimeyer et al (in press)…”
Section: Resultsmentioning
confidence: 99%
“…Survey results for commitment to change are limited because they are self-reported. Nevertheless, self-reported commitment is a valid predictor of behavioral change in practice and provides a useful surrogate measure in the absence of observational data 23 , 24 . Although the proportion of participants who responded to the post-activity 30-day survey was relatively small, it was representative of the activity completers in terms of profession and specialty and provided a useful indication of implementation relative to learning and stated commitment.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of the relationship between reflection and behavior change in continuing medical education provides further evidence in this regard (Ratelle et al, 2017). In a cohort study of attendees at a continuing medical education course at a national hospital, 223 participants rated the level of reflection that was generated from them in relation to each presentation they attended, and formulated commitment-to-change statements at the conclusion of each course.…”
Section: Facilitating Learning Through Commitments To Change (Ctcs)mentioning
confidence: 96%
“…In addition, higher reflection scores were related to the greater availability of opportunities for audience response and the use of clinical case illustrations. The researchers concluded that “we found that reflection strongly correlates with CTC” and that “continuing education curricula that stimulate reflections may actually promote positive patient care behaviors” (Ratelle et al, 2017, p. 166).…”
Section: Facilitating Learning Through Commitments To Change (Ctcs)mentioning
confidence: 99%